Examining the effect of motivation on the influence of human resource practices and normative commitment among SMEs in Selangor / Elaina Rose Johar ... [et al.] - Johar, Elaina Rose; Mat Nor, Norzanah; Hassan, Roshidi; Musa, Rusnifaezah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
Human resources are vital to the success or failure of the organization. However, there exist challenges in maintaining these human resources although human resource practices are deliberated as an important factor to improve employees’ commitment to the organization.  Hence, this study aimed to investigate the nature of relationship that exists between human resource practices and normative commitment with motivation as the mediator. Employed a quantitative research approach, 64 SME employees in Selangor were surveyed. It was found that all human resource practices have positive effect on normative commitment with compensation, training and employee involvement-decision being significant. This study also revealed that motivation has a mediating effect for the relationship of training and both employee involvement with normative commitment. Thus, it can be concluded that both training and employee involvement create sense of loyalty and obligation to stay when employees are motivated.